Natural and anthropogenic dynamics of Artemisia terrae-albae Krasch. communities in the Northern Aral region (Eurasian Journal of Ecology, 2025)
The article examines the dynamic processes occurring in the zonal Artemisia terrae-albae Krasch. communities of the Northern Aral region. Factors of natural and anthropogenic dynamics have been identified. B.A. Bykov's con-association was chosen as a key concept to illustrate the indigenous and variable vegetation conditions within a genetically homogeneous territory. The natural association is ephemeroid-sagebrush with Anabasis aphylla L. (Artemisia terrae-albae, Rheum tataricum L.f., Poa bulbosa L., Catabrosella humilis (M.Bieb.) Tzvelev). The natural dynamics of Artemisia terrae-albae communities is determined by endoecogenetic successions caused by the vital activity of dominants and subdominants of communities and exogenous successions associated with local soil erosion and the appearance of micro-depressions with Stipa sareptana A.K.Becker and S. lessingiana Trin. & Rupr. microcenoses.Anthropogenic dynamics is caused by pasture and road digression. During grazing, the dominant role Artemisia terrae-albae passes to Anabasis aphylla, an indicator of disturbance. Road digression leads to the replacement of natural communities by annual saltwort, ephemeral, Polygonum aviculare L. aggregations and procenoses on a technogenic relief. The change of Artemisia terrae-albae to Poa bulbosa communities has a mixed natural and anthropogenic origin. The release of ecological niches for the colonization of Poa bulbosa occurs as a result of grazing, the formation of field roads and the death of Artemisia terrae-albae as a result of natural aging. The revealed patterns of natural and anthropogenic dynamics form the basis for the development of measures for sustainable use and development of natural resources of the territory.Key words: succession, conassociation, zonal vegetation, Poa bulbosa, digression, ecological niche.